Public Test Flyer Model for Language Services on Language Errors in Semester VII Indonesian Language and Literature Education Study Program Al Washliyah Muslim University of Nusantara - Nirmawan, Nirmawan; Hasibuan, Abdullah; Sutarini, Sutarini (Westscience Press, 2025)
This flyer media will be used in teaching language error analysis to identify errors in flyers as a promotion that is still relied upon today. Language error analysis is used by language teachers to collect error samples, identify errors in the samples, explain the errors, classify errors, and evaluate the level of seriousness of the errors. The purpose of this study is to find out how to conduct language error analysis and what language should actually be used in flyer media during promotions. This type of research is descriptive research with a qualitative approach. This research was conducted on seventh-semester students of the PBSI Study Program at UMN Al Washliyah. The population in this study was all seventh-semester PBSI students, totaling 18 people. The sampling technique used in this study was a non-probability sampling technique. The outputs of this research are Accredited National Journal Publications, National Proceedings of Research Results of LP2M UMN Al-Washliyah, and Monograph Books. The follow-up of this research creates a comprehensive workflow from research results to real implementation and continuous improvement. Through collaboration between universities and research partners, this research has the potential to create positive and sustainable changes in various aspects of community life.